2021
DOI: 10.1186/s12885-021-09067-x
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and risk of cancer: a Mendelian randomization study

Abstract: Background Previous large observational cohort studies showed higher blood pressure (BP) positively associated with cancer. We used Mendelian randomization (MR) to obtain less confounded estimates of BP on total and site-specific cancers. Methods We applied replicated genetic instruments for systolic and diastolic BP to summary genetic associations with total cancer (37387 cases, 367856 non-cases) from the UK Biobank, and 17 site-specific cancers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Finally, when palindromic SNPs existed, we used the allele frequency information to infer the forward-strand alleles. We used a curated genotype-phenotype database (PhenoScanner) to search for associations between variants used to detect each instrumental variable and other traits that may represent pleiotropic pathways; specific examples are traits associated with hypertension and telomere length, which are recognized risk factors for cutaneous melanoma ( 18 , 19 ). Variants associated with these and other traits were excluded from sensitivity analysis (using a software default threshold of P< 5 × 10 – 8).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, when palindromic SNPs existed, we used the allele frequency information to infer the forward-strand alleles. We used a curated genotype-phenotype database (PhenoScanner) to search for associations between variants used to detect each instrumental variable and other traits that may represent pleiotropic pathways; specific examples are traits associated with hypertension and telomere length, which are recognized risk factors for cutaneous melanoma ( 18 , 19 ). Variants associated with these and other traits were excluded from sensitivity analysis (using a software default threshold of P< 5 × 10 – 8).…”
Section: Methodsmentioning
confidence: 99%
“…Mendelian randomization (MR) is an approach integrating summary data of genome-wide association studies (GWAS) to estimate the causal link between risk factors and outcomes [ 11 ]. Genetic polymorphisms that are randomly assigned at conception are used in MR design as instrumental variables, which can fill in the gaps in the evidence by reducing confounding variables [ 12 ]. MR method must conform to three important assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…There is inconsistent evidence regarding the association of hypertension and cancer risk. 9 , 10 In observational studies, hypertension was associated with increased cancer risk. However, in a Mendelian randomization analysis using genetic variants to explore causality, blood pressure did not appear to be a causal risk factor for cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a Mendelian randomization analysis using genetic variants to explore causality, blood pressure did not appear to be a causal risk factor for cancer. 10 Renin-angiotensin-system (RAS) plays a pivotal role in the regulation of blood pressure through formation of angiotensin-II which is one of the most potent vasoconstrictors with pro-inflammatory effects. Experimental and clinical studies suggested that gluco-lipotoxicity could activate angiotensin-II with increased angiogenesis and cellular adhesion, invasion and proliferation which might promote cancer risk.…”
Section: Introductionmentioning
confidence: 99%